Analisis Pengaruh Corporate Governance, Profitabilitas, dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2022. - Yamin, Mohammad; Lita Anggraini, Nabila (Accounting Research and Business Journal, 2024)
Purpose: This research aims to determine the influence of corporate governance, profitability and leverage on earnings management in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Design/methodology/approach: The data source used is secondary data in the form of company financial reports with samples determined by purposive sampling. Where 12 companies were obtained as samples from a population of 42 companies in the food and beverage sector. The research method used is multiple linear regression analysis including the classical assumption test, partial test (t), and simultaneous test (F). Findings: The research results show that partially the company size and leverage variables have no effect on earnings management, the audit committee variables and profitability have a significant effect on earnings management. Simultaneously, the variables company size, audit committee, profitability and leverage influence earnings management. The adjusted r-squared value in this study was 72.7% while the remaining 27.3% was influenced by other variables not used in this study.